N471D WASH complex subunit strumpellin knock‐in mice display mild motor and cardiac abnormalities and BPTF and KLHL11 dysregulation in brain tissue. (12th August 2021) - Clemen, Christoph S.; Schmidt, Andreas; Winter, Lilli; Canneva, Fabio; Wittig, Ilka; Becker, Lore; Coras, Roland; Berwanger, Carolin; ,; Hofmann, Andreas; Eggers, Britta; Marcus, Katrin; et al.
Abstract: Aims: We investigated N471D WASH complex subunit strumpellin ( Washc5 ) knock‐in and Washc5 knock‐out mice as models for hereditary spastic paraplegia type 8 (SPG8). Methods: We generated heterozygous and homozygous N471D Washc5 knock‐in mice and subjected them to a comprehensive clinical, morphological and laboratory parameter screen, and gait analyses. Brain tissue was used for proteomic analysis. Furthermore, we generated heterozygous Washc5 knock‐out mice. WASH complex subunit strumpellin expression was determined by qPCR and immunoblotting. Results: Homozygous N471D Washc5 knock‐in mice showed mild dilated cardiomyopathy, decreased acoustic startle reactivity, thinner eye lenses, increased alkaline phosphatase and potassium levels and increased white blood cell counts. Gait analyses revealed multiple aberrations indicative of locomotor instability. Similarly, the clinical chemistry, haematology and gait parameters of heterozygous mice also deviated from the values expected for healthy animals, albeit to a lesser extent. Proteomic analysis of brain tissue depicted consistent upregulation of BPTF and downregulation of KLHL11 in heterozygous and homozygous knock‐in mice. WASHC5‐related protein interaction partners and complexes showed no change in abundancies. Heterozygous Washc5 knock‐out mice showing normal WASHC5 levels could not be bred to homozygosity. Conclusions: While biallelic ablation of Washc5 was prenatally lethal, expression of N471D mutated WASHC5 led to several mild clinical and laboratory parameter abnormalities, but not to a typical SPG8 phenotype. The consistent upregulation of BPTF and downregulation of KLHL11 suggest mechanistic links between the expression of N471D mutated WASHC5 and the roles of both proteins in neurodegeneration and protein quality control, respectively. Abstract : N471D WASH complex subunit strumpellin ( Washc5 ) knock‐in mice showed mild dilated cardiomyopathy, gait abnormalities, and other clinical and laboratory parameter deviations, but not a typical hereditary spastic paraplegia type 8 phenotype. Both Washc5 knock‐in and heterozygous knock‐out mice showed normal WASHC5 levels, but biallelic ablation of Washc5 was prenatally lethal. In brain tissue of Washc5 knock‐in mice, upregulation of BPTF and downregulation of KLHL11 mechanistically links mutated WASHC5 with roles of BPTF and KLHL11 in neurodegeneration and protein quality control.